Analysis of outcomes and reasons for refusing organs offered by the National Transplant Center - Patricia Freire; Carmelia Matos Santiago Reis; Maria Rita Carvalho Garbi Novaes (Einstein (São Paulo))
ABSTRACT Objective: To investigate the outcomes and reasons for the refusal of organs offered on a single national list managed by the National Transplant Center. Methods: This retrospective cohort study was conducted with a quantitative approach, using data from offers of organs not used in the states and the Federal District, but offered to the National Transplant Center for national distribution. Results: Of the 22,824 offers of unused organs in the states to the National Transplant Center, 8,483 (37%) were accepted and 14,341 (63%) refused. Of the accepted organs, 6,433 (76%) were implanted and 2,050 (24%) were not used. Conclusion: The use of organs at the interstate (national) level could be improved, and ascertaining the reasons for refusal could contribute to intervention strategies.